Fish in the diet of peasants of the Russian North: Ethnolinguistic aspect - K. V. Osipova (Шаги, 2022)
In the article, on the basis of ethnolinguistic analysis, the role of fish in the diet of the peasants of the Arkhangelsk and Vologda regions is determined: the composition of the fish diet, the unique food preferences of certain groups of the population, the cultural and linguistic symbolism of fish diet are revealed. Lexicographic files of the Ural Federal University Toponymic Expedition, as well as dialect dictionaries covering the Northern Russian territories were the main source of the material. We discuss the names of the dishes (zharega, ukha po balkam, treskovik, latka, molevatik, etc.), the methods of cooking, storing and eating fish (mezhonnaia ryba, ryba s dushkom; syrkom, machko, ryba machkom, etc.), as well as nicknames that go back to ichthyonyms. Under the conditions of artel-based fishing and the need to sell the catch or hand it over to the state, valuable fish rarely appeared on peasant tables, which resulted in the popularity of dishes from ruffs and other small fish. Analysis of collective anthroponyms allows us to determine the main types of fish consumed: ruffs — ersheedy, ershegloty, smelt — riapusa, koriushin’ia, cod — treskoedy, etc. Nicknames record local food habits, for example, the use of lightly salted or pickled fish (syroedy, kislaia kambala), which were formed under the influence of the Finno-Ugric culinary tradition. The specificity of the fish diet was a marker that differentiated local groups of the population, drawing the boundaries between “their own” food and that of “others”, “urban” and rural, etc. Anthroponyms also reflect the opposition between peasant farmers, whose diet consisted of farinaceous dishes, and residents of villages who were engaged in fishing (testoedy, oparniki — khaiduki-fishermen).